2015
DOI: 10.3390/atmos6111785
|View full text |Cite
|
Sign up to set email alerts
|

pH Control in Fog and Rain in East Asia: Temporal Advection of Clean Air Masses to Mt. Bamboo, Taiwan

Abstract: Fog and rain was collected during an 18-day period in January 2011 at Mt. Bamboo, northern Taiwan. Almost 300 hourly fog samples and 16 daily rain samples were taken. One single fog sample (pH 3.17) was influenced by local volcanic activity, otherwise the pH ranged from 3.23 to 6.41 in fog and from 3.59 to 6.31 in rain. All the respective air masses arrived from the northeast, but exhibited two distinct groups: Group_1 had high concentrations of all ions (median interquartile range of total ion concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…In many studies, calcium (Ca 2+ ) has been found to be a major chemical component of fog water, mainly due to mineral dust from construction sites (Li et al, 2011) and land erosion (Liu et al, 2010;Klemm et al, 2015). However, in our study Ca 2+ contributes only slightly to the TIC, with a median of 3.7 ± 4.2%.…”
Section: Ionic Composition and Eccontrasting
confidence: 59%
See 3 more Smart Citations
“…In many studies, calcium (Ca 2+ ) has been found to be a major chemical component of fog water, mainly due to mineral dust from construction sites (Li et al, 2011) and land erosion (Liu et al, 2010;Klemm et al, 2015). However, in our study Ca 2+ contributes only slightly to the TIC, with a median of 3.7 ± 4.2%.…”
Section: Ionic Composition and Eccontrasting
confidence: 59%
“…As shown in many previous studies, H 2 SO 4 and HNO 3 are the main acidifiers in fog water (e.g., Li et al, 2011;Degefie et al, 2015;Klemm et al, 2015;Simon et al, 2016). To measure the non-neutralized acidity of fog water, Hara et al (1995) proposed the quantitative index pAi, which is defined as the negative decimal logarithm of the nss-SO 4 2-concentration plus the NO 3 -concentration (Eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeta potentials for PC membranes showed the greatest differences at pH values from 2.5 to 6, which is in the range of water harvested from typical fogs around the world (3.5−6 pH). 50,51 The highest level of zeta potential was observed for PC25+, with the lowest surface charge measured with KPFM. Interestingly, for pH values above 7, the difference in the zeta potential of the tested samples ceased to show significant changes.…”
Section: Resultsmentioning
confidence: 95%